1997
DOI: 10.1007/s004030050223
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the retinoid-inducible polypeptide, midkine, in human epidermal keratinocytes

Abstract: Midkine (MK) is a retinoid-inducible and potent cell growth/differentiation factor active during mouse embryogenesis. We studied MK expression in various cell strains established from the skin. MK and its mRNA were detected in cultured keratinocytes but not in melanoma cell lines or dermal fibroblasts by both Western blot analysis and reverse transcription-polymerase chain reaction (RT-PCR). Treatment of cultured keratinocytes with retinoic acid (10(-5) M, 24 h) resulted in an increase in the level of MK mRNA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
0
23
3
Order By: Relevance
“…Midkine is a heparin-binding growth/differentiation regulating factor that promotes neuronal growth (54,55). Its expression in human epidermal keratinocytes was also associated to promoted growth (56). On the basis of elevated serum levels in cancer patients (57), the possibility of selective expression in the immortal and malignant states indicates an association also to the development of oral squamous carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Midkine is a heparin-binding growth/differentiation regulating factor that promotes neuronal growth (54,55). Its expression in human epidermal keratinocytes was also associated to promoted growth (56). On the basis of elevated serum levels in cancer patients (57), the possibility of selective expression in the immortal and malignant states indicates an association also to the development of oral squamous carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…This result may indicate that the nucleolin is related to the direct or indirect regulation of the transcription of the MK gene. MK is a multifunctional heparin-binding growth factor expressed in various cell types during embryogenesis (37). Enamel organ formation and cell differentiation were both inhibited in cultured tooth germ by adding the neutralizing antibodies for MK to the culture media (38), thus showing the MK to be an indispensable factor for tooth germ development.…”
Section: Discussionmentioning
confidence: 99%
“…66 The gene expression profiling pattern indicated that MK has a pleotrophic effect on squamous epithelial cells affecting genes implicated in diverse pathways as protein biosynthesis, cell motility, cytoskeleton and tissue remodeling, plasma membrane metabolism, receptor reorganization and cytokine signaling. 24,59 Therefore, we suggest that the MK-Notch2-Stat3 pathway contributes to EMT, which is one of the important component of neonatal and tumor development. [5][6][7][8][9][10]31,[37][38][39][40][60][61][62][63] Since EMT plays a specific role in the migration of cells from a primary tumor into the circulation [1][2][3][4] an improved understanding of the role of MK-Notch2-Stat3 signaling in the EMT may provide a rationale for developing additional targeted cancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] Overexpression of the full-length MK and MKC (C-terminal truncated isoform) promoted tumorigenesis in vitro and in vivo. 15,16 Since MK can promote various cellular processes (e.g., cell proliferation, survival, migration, angiogenesis, drug resistance and antiviral action) associated with cancer development, [17][18][19][20][21][22][23][24][25] identification of function-specific receptors should become an important task.…”
Section: Introductionmentioning
confidence: 99%